Online impressions on e-hailing services: A study of positive and negative sentiments on Grab Malaysia and Go-Jek Indonesia on twitter platform - Chow, Emily Yan Chi (2019)
The presence of mobile-internet has leads to the emergence of e-hailing industry. The increase usage in e-hailing services has led riders to share their opinions or discontent after indulging in the services. Therefore, in this study, online sentiments on social media (Twitter) were examined to identify the rider opinions towards the e-hailing services in both Malaysia and Indonesia. Service Quality (SERVQUAL) model was used as the foundation to examine the service quality offered by the ehailing service providers. The dimensions used were: ‘availability’, ‘accessibility’, ‘information’, ‘comfort’, ‘safety’, and ‘price’. All the data collected were classified into either a positive or negative sentiment, and the results revealed that all the dimensions show a negative trend in both countries. ‘Comfort’ and ‘availability’ was ranked the first in Malaysia and Indonesia respectively. The result showed riders concerned the most the in dimensions of ‘availability’ and ‘comfort’ due to riders demanded an e-hailing service that is available anywhere and anytime when they need it. The study results provide a strong reference to practitioners to improve on their service quality and allowed to identify which dimensions were concerned the most by the riders in both countries.